Distal Bypass Surgery for Critical Ischemia Using a Related Donor Vein - V. V. Karpov; R. E. Kalinin; I. A. Suchkov; A. A. Egorov; O. V. Zaitsev; А. S. Pshennikov; D. V. Karpov (Неотложная медицинская помощь, 2024)
The article presents a case of using the trunk of the great saphenous vein from a living related donor in elective surgery for the main arteries of the lower leg. The possibility of using a vein from a relative in special clinical situations is shown. High risks of repeated interventions aimed at relieving early and late complications of vascular reconstructions remain an urgent problem in angiosurgery. Very often, operations are performed in the presence of extensive necrosis and trophic ulcers (stage IV according to the Fontaine-Pokrovsky classification). The gold standard for choosing a shunt during reconstructive operations on the infrainguinal arteries was and remains an autovenous conduit from the great saphenous vein (C, D type of arterial bed lesion according to TASC II). During repeated reconstructions in the absence of a suitable autovein and with the distal position of the peripheral anastomosis, it is not always possible to use a synthetic prosthesis as a reliable alternative. Unsatisfactory Results of using such materials dictate the need to choose a suitable graft. The problem of using allografts requires further in-depth study. In this regard, the case of using a donor vein as a material for reconstruction is given. It was concluded that it is possible to effectively use allovein from a related donor in a patient after previously performed reconstructive interventions and in the absence of autologous material for bypass surgery.